Voting in small networks with cross-pressure - Ascensión Andina-Díaz; Miguel A. Meléndez-Jiménez (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
We present a model of participation in elections in small networks, in which citizens suþer from cross-pressures if voting against the alternative preferred by some of their social contacts. We analyze how the existence of cross-pressures may shape voting decisions, and so, political outcomes; and how candidates may exploit this eþect to their interest.
Keywords: D72; 330; Network; voting; cross-cutting; Wahlverhalten; Soziales Verhalten; Soziales Netzwerk; Gleichgewicht; Nichtkooperatives Spiel; Theorie